Assessment of facility performance during mass treatment of chronic hepatitis C in Egypt: Enablers and obstacles. Issue 9 (September 2020) - Shousha, Hend Ibrahim; Said, Mohamed; ElAkel, Wafaa; ElShafei, Arwa; Esmat, Gamal; Waked, Emam; Elsayed, Manal Hamdy; Doss, Wahid; elrazky, Maysa; Mehrez, Mai; Hassany, Mohamed; zeyada, Dina; et al.
Abstract: Background: The national committee for control of viral hepatitis (NCCVH) in Egypt, settled by the Ministry of health, treated over one million patients in around 60 centers with chronological changes in drug combinations. This research aims to study the health care facilities and services provided by NCCVH treatment centers in Egypt and explore hinders faced. Methods: A cross-sectional operational research study. Multistage random sampling technique was applied for Egyptian governorates. From each stratum one governorate was chosen from which one center was randomly selected. Quality of recorded data for each center in the central server (Data-oriented parameter), newly designed score to assess the overall performance of the centers was retrieved from computer based recording system. A self-administered questionnaire was completed by the centers head. Results: This study included 24 treatment centers from urban, rural areas, Upper and Lower Egypt. The Upper centers showed the best completeness of follow-up records and the least compliance rates. None of the centers had 100% completeness of follow-up data. Proportion of SVR is minimally less than proportion of patient with known outcome in all treatment centers. A novel indicator standardizing the comparisons of performance of different facilities was introduced: Total number of physicians/total number of SVR patients with completed records. The highest response rate: Monfiya Governorate (Lower Egypt), Aswan (Upper Egypt), Completeness of follow-up records: Kalyoubia (Lower Egypt), Sohag governorate (Upper Egypt). The average administrative score was 64%. Conclusion: Challenges of NCCVH program: overcrowdings, resistant sociocultural background among rural patients, limited accessibility for internal migrants and incompleteness of data entry are system lacking points. Strengths include, clear patient pathway, well-established database online application, well-trained physicians and treatment availability.